Amyloid-β (1-40) and mortality in patients with non-ST-segment elevation acute coronary syndrome: a cohort study - Stamatelopoulos, Kimon; Müller-Hennessen, Matthias; Georgiopoulos, Georgios; Sachse, Marco; Boeddinghaus, Jasper; Sopova, Kateryna; Gatsiou, Aikaterini; Amrhein, Carolin; Biener, Moritz; Vafaie, Mehrshad; Athanasouli, Fani; Stakos, Dimitrios; et al. (Annals of internal medicine, 2018)
Background: Amyloid-β (1-40) (Aβ40) is implicated in mechanisms related to plaque destabilization and correlates with adverse outcomes in stable coronary artery disease. - Objective: To determine the prognostic and reclassification value of baseline circulating levels of Aβ40 after adjustment for the Global Registry of Acute Coronary Events (GRACE) score, which is widely recommended for risk stratification in non-ST-segment elevation acute coronary syndrome (NSTE-ACS). - Design: Retrospective cohort study using data from 2 independent prospective cohorts, the Heidelberg study (n = 1145) and the validation multicenter international APACE (Advantageous Predictors of Acute Coronary Syndrome Evaluation) study (n = 734). - Setting: Academic hospitals in 7 European countries. - Participants: Patients with adjudicated NSTE-ACS followed for a median of 21.9 and 24.9 months in the Heidelberg and APACE studies, respectively. - Measurements: All-cause mortality was the primary end point. - Results: Amyloid-β (1-40) was associated with mortality after multivariate adjustment for age, sex, diabetes mellitus, high-sensitivity cardiac troponin T and C-reactive protein, revascularization, and ACS type (Heidelberg cohort hazard ratio [HR] for 80th vs. 20th percentiles, 1.66 [95% CI, 1.06 to 2.61; P = 0.026]; APACE cohort HR, 1.50 [CI, 1.15 to 1.96; P = 0.003]). It was also associated with mortality after adjustment for the GRACE score (Heidelberg cohort HR for 80th vs. 20th percentiles, 1.11 [CI, 1.04 to 1.18; P = 0.001]; APACE cohort HR, 1.39 [CI, 1.02 to 1.88; P = 0.036]). Amyloid-β (1-40) correctly reclassified risk for death over the GRACE score (net reclassification index, 33.4% and 47.1% for the Heidelberg and APACE cohorts, respectively) (P < 0.05). - Limitation: At low concentrations of Aβ40, dose-response associations with mortality differed between cohorts, possibly because of varying blood preparations used to measure Aβ40. - Conclusion: Circulating Aβ40 is a predictor of mortality and improves risk stratification of patients with NSTE-ACS over the GRACE score recommended by clinical guidelines. The clinical application of Aβ40 as a novel biomarker in NSTE-ACS should be further explored and validated. - Primary Funding Source: German Cardiac Society.
Gesehen am 08.04.2020